Sense of Humor Dr. (HC) KH. Ahmad Hasyim Muzadi pada Acara Reuni Akbar 90 Tahun Pondok Gontor - Waluyo Satrio Adji (Piwulang: Jurnal Pendidikan Agama Islam, 2019)
KH. Hasyim Muzadi is a person who has the Sense of humor, this was evidenced in his lecture at the grand reunion 90 years of Pondok Gontor. Sense of humor becomes an effective method for conveying a message or value. The approach in this study uses a descriptive type qualitative approach. The data in this case is the Sense of Humor lecturer, while the source of the data is the lecture KH.Hasyim Muzadi in the grand reunion event of 90 years Pondok Gontor. The analysis used is qualitative descriptive analysis. The results in this study that the element of Sense of Humor is owned by KH Hasyim Muzadi during the lecture, the aspect of Sense of Humor used dominantly on the aspect of innuendo or criticism and aspects of a funny story. The type of Sense of Humor used is the intellectual type of humor, because of the intellectual background of the speaker.